MAPPING APATITE-ILMENITE RARE EARTH ELEMENT MINERALIZED ZONE USING FUZZY LOGIC METHOD IN SIJUK DISTRICT, BELITUNG - Muhamad Iqbal Januadi Putra; nFN Sobirin (National Institute of Aeronautics and Space of Indonesia (LAPAN), 2018)
District of Sijuk located in Belitung Island is rich with non-lead mineral content. As the part of Southeast Asia’s Lead Belt, the presence of Apatite-Ilmenite Rare Earth Element formed by the region’s geological condition is very likely. However, there has not been any activity to map and identify the apatite-ilmenite distribution in this region. Therefore, the objective of this study was to map the mineralized apatite-ilmenite in Sijuk District. Using remote sensing technology, Landsat 8 OLI were utilized to map the distribution of mineralized apatite-ilmenite rare earth element. Alteration mineral carrier, geological structure, and lithology data were all used as variables. Landsat-8 was pre-processed using band ratio and Directed Principal Component Analysis (DPCA) method for gaining alteration variable. The fuzzy logic method was then deployed for integrating all data. The result of this research showed the potential distribution of mineralized apatite-ilmenite with a total area of 1,617 ha. The most prioritized areas for apatite-ilmenite mineral exploitation are located in Air Seruk Village’s IUP (Izin Usaha Pertambangan/Mining Business License), Sijuk Village’s IUP, and Batu Itam Village’s IUP. This study also illustrates the orientation of the metal utilization of apatite-ilmenite in district Sijuk.